"One-pot" aminolysis/thia-Michael addition preparation of well-defined amphiphilic PVDF-b-PEG-b-PVDF triblock copolymers: self-assembly behaviour in mixed solvents. Issue 2 (11th September 2019) - Folgado, Enrique; Guerre, Marc; Da Costa, Antonio; Ferri, Anthony; Addad, Ahmed; Ladmiral, Vincent; Semsarilar, Mona
Abstract : Novel amphiphilic PVDF-based triblock copolymer (PVDF50 - b -PEG136 - b -PVDF50 ) is synthesized using RAFT polymerization and a one-pot thia-Michael addition. Self-assembly of this ABA copolymer resulted in formation of original crystalline structures. Abstract : Polyvinylidene fluoride- (PVDF) containing block copolymers are scarce and difficult to prepare. Amphiphilic block copolymers containing PVDF have been rarely reported. In consequence, few studies of the self-assembly of PVDF-based block copolymers exist. Here a new synthetic route to prepare poly(vinylidene fluoride)- block -poly(ethylene glycol)- block -poly(vinylidene fluoride) (PVDF- b -PEG- b -PVDF) ABA triblock copolymer is presented. The synthesis relies on the efficient coupling of a PVDF prepared by RAFT and a PEG diacrylate in one pot via aminolysis of the xanthate moiety and subsequent thia-Michael addition. The novel amphiphilic triblock copolymer was fully characterized by 1 H and 19 F NMR spectroscopies, GPC, TGA, DSC and XRD; and its self-assembly in water and ethanol was studied. Micellization (addition of a selective solvent for PVDF to a solution of the triblock) and nanoprecipitation (addition of a solution of the triblock into a non solvent of PVDF) protocols led to the formation of micelles and vesicles. Surprisingly, under nanoprecipitation conditions (in THF/ethanol), well-defined crystalline micrometric structures were obtained.